Bioenergy in the IPCC Assessments. Issue 7 (27th April 2018) - Smith, Pete; Porter, John R.
Abstract : Estimates of total global climate change mitigation potential of bioenergy have varied between IPCC AR1 to AR5 (including SRREN). Ranges are shown where given (for different carbon prices from AR3 onwards), and the point in the range for AR5 corresponds to the mean potential for BECCS in 2100 for scenarios consistent with a 2°C target from the IPCC AR5 WGIII scenario database